Bioremediation of Polluted Water with Crude Oil in South Baghdad Power Plant - Yasin, Akram; Salman, Shihab; Al-Mayaly, Ithar (Iraqi Journal of Science, 2023)
Pseudomonas aeruginosa and Klebsiella pneumoniae appears good growth when replicate to culture with heavy crude oil. K. pneumoniae was less ability to biodegrade the heavy crude oil (66.22 wt.%) compare with P. aeruginosa 74 wt.%). Also the emulsion percent were about 64.8 % and 62.5 % for K. pneumoniae and P. aeruginosa, respectively. The results showed that the emulsions produced from both the strains decrease the surface tension of the media from 68.43 Mn/m (for control sample) to 44.50 and 43.30 Mn/m for P. aeruginosa and K. pneumoniae, respectively. The optimum temperature and pH for the hydrocarbons biodegradation were 28 ºC and 7, respectively. The incubation period of 28 days of the isolated increased hydrocarbons biodegradation, which were (78 %) for P. aeruginosa, and (83 %) for K. pneumoniae. While, P. aeruginosa recorded heavy oil biodegradation percents were 76.94 and 71.73 % for oil concentrations 1000 and 2000 mg/l, respectively. While the percentage of biodegradation by K. pneumoniae to heavy oil were 74.87 and 69.92 % for 1000 and 2000 mg/l, respectively.